2015
DOI: 10.3390/agriculture5020155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ozone Treatment on Inactivation of Escherichia coli and Listeria sp. on Spinach

Abstract: Abstract:The efficacy of "gaseous" ozone in reducing numbers and re-growth of food-borne pathogens, (Escherichia coli and Listeria spp.), on leafy salads was investigated using spinach. A preliminary in vivo study showed 1-log reduction in six strains of E. coli and two species of Listeria spp. on spinach exposed to 1 ppm ozone for 10 min. A range of ozone treatments were explored to deliver optimal bacterial inactivation while maintaining the visual appearance (color) of produce. Exposure to a higher ozone co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
19
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
6
19
1
7
Order By: Relevance
“…Interestingly, some individual cells on the leaf surface also survived ozone treatment 304 suggesting that they also have inherent resistance mechanisms. We hypothesised that the 305 survival of the individual bacteria on the leaf surface after ozone exposure is due to ageing or 306 prior exposure to cold (Johnson, 2008;Wani et al, 2015).…”
Section: Effect Of Age On Ozone Resistance Of the Leaf Surface Bactermentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some individual cells on the leaf surface also survived ozone treatment 304 suggesting that they also have inherent resistance mechanisms. We hypothesised that the 305 survival of the individual bacteria on the leaf surface after ozone exposure is due to ageing or 306 prior exposure to cold (Johnson, 2008;Wani et al, 2015).…”
Section: Effect Of Age On Ozone Resistance Of the Leaf Surface Bactermentioning
confidence: 99%
“…leaf surface bacteria(Wani et al, 2015). Fresh produce typically takes weeks to grow and any 326 cells present on the leaf surface could easily have been present and persisting for a prolonged 327 period.…”
mentioning
confidence: 99%
“…Tailing effect was observed with the increase in treatment time. The assumption is that a certain population of bacteria remains resistant to ozone due to the adaptation of microorganisms to certain stresses (Van Boekel, 2002;Wani et al, 2015Wani et al, , 2016. Additionally, the flow rate in the present study was slow (1 L/min) which may limit the gas exchange on the strawberries' surfaces.…”
Section: Discussionmentioning
confidence: 92%
“…Studies on baby spinach showed 1-log reduction of E. coli and Listeria spp. after being exposed to 10 ppm ozone gas for 2 min (Wani et al, 2015). As ozone sensitivity is commodity dependent, it is important to establish optimal application conditions for each food commodity (Karaca, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To address safety and spoilage issues of fresh produce, a number of decontamination methodologies for fresh produce have been reported (10,11). Current chemical treatments such as chlorine, peroxyacetic acid, hydrogen peroxide, quaternary ammonium, and ozone are effective in reducing the microbial load in wash water but have limited efficacy for inactivation of bacteria on fresh produce surfaces (1-to 2-log reduction) (12)(13)(14)(15). This limitation is due to nonspecific consumption of sanitizers upon reactions with the food matrix (16).…”
mentioning
confidence: 99%